A composite control scheme for electromagnetic active mass damper against control-structure-interaction effects. (15th April 2023) - Yao, Hongcan; Tan, Ping; Zhou, Huimeng; Zhou, Fulin
Highlights: CCS comprised of force compensation and hierarchical control is proposed. Frequency response tests and shake table tests are conducted to verify CCS. The CSI effects of electromagnetic AMD are significantly reduced by CCS. CCS decouples the AMD tracking control from the structural control design. Abstract: Existing methods account for control-structure-interaction (CSI) in structural control design. However, their implementations may be challenging since the dynamic characteristics of actuator are unavailable in the preliminary design phase of actively controlled structures. In this study, a composite control scheme (CCS) is proposed to eliminate the CSI effects of electromagnetic active mass damper (AMD), and thus decouple the tracking control of AMD from the control design of structure. In the CCS, force compensation is performed to counteract the influence of lower-order CSI including the damping force and friction, while hierarchical control comprised of low-level feed-forward/feedback control and high-level sliding mode control is designed to reduce the higher-order CSI effect and achieve a high-performance force control. Performance tests and frequency response tests of the electromagnetic AMD system indicate that the CSI effects are significantly reduced by the proposed CCS. Furthermore, shake table tests are conducted on a two-story actively controlled structure to verify the effectiveness of CCS. Experimental results show that the proposed CCS can apply accurate control force to the structure, which contributes to an ideal structural response control.